Pseudorotations of the 2-disc and Reeb flows on the 3-sphere - Albers, Peter; Geiges, Hansjörg; Zehmisch, Kai (Ergodic theory and dynamical systems, 2022)
We use Lerman’s contact cut construction to find a sufficient condition for Hamiltonian diffeomorphisms of compact surfaces to embed into a closed -manifold as Poincaré return maps on a global surface of section for a Reeb flow. In particular, we show that the irrational pseudorotations of the - -disc constructed by Fayad and Katok embed into the Reeb flow of a dynamically convex contact form on the - -sphere.
Published online by Cambridge University Press: 18 March 2021
Gesehen am 12.07.2022